Dialogues, Trialogues and Triangles: The Geometry of Germany's Foreign Policy of Trust-Building. Issue 2 (3rd April 2017) - Yoder, Jennifer A.
Abstract : This article explores three formats for interstate relations developed by, or at least significantly influenced by Germany in the post-Cold War period: the Petersburg Dialogue, the German–Russian–Polish Trialogue and the Weimar Triangle. An examination of the form and function of each of these formats is followed by a discussion of what these formats have in common and why they are worthy of further study. The paper addresses whether this 'variable geometry' of Germany's foreign policy of trust-building is likely to survive a period of turbulent relations or changes in leadership and, furthermore, how the effectiveness of dialogues, trialogues and triangles might be evaluated.